2017
DOI: 10.12688/f1000research.11057.1
|View full text |Cite
|
Sign up to set email alerts
|

Immunosurveillance by human γδ T lymphocytes: the emerging role of butyrophilins

Abstract: In contrast to conventional T lymphocytes, which carry an αβ T-cell receptor and recognize antigens as peptides presented by major histocompatibility complex class I or class II molecules, human γδ T cells recognize different metabolites such as non-peptidic pyrophosphate molecules that are secreted by microbes or overproduced by tumor cells. Hence, γδ T cells play a role in immunosurveillance of infection and cellular transformation. Until recently, it has been unknown how the γδ T-cell receptor senses such p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 94 publications
(133 reference statements)
0
13
0
Order By: Relevance
“…Specifically, exercise increases the proportions and absolute number of non-classical monocytes, which release higher levels of pro inflammatory cytokines (e.g., TNF-α and IL-18) that are essential for the activation and expansion of Vγ9Vδ2 T-cells (51). Moreover, the activation of Vγ9Vδ2 T-cells by ZOL and IPP requires expression of butyrophilin BTN3A molecules on monocytes (52), which could also be affected by exercise. Future studies should determine the role monocytes play in activating and expanding TCR-γδ T-cells after exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, exercise increases the proportions and absolute number of non-classical monocytes, which release higher levels of pro inflammatory cytokines (e.g., TNF-α and IL-18) that are essential for the activation and expansion of Vγ9Vδ2 T-cells (51). Moreover, the activation of Vγ9Vδ2 T-cells by ZOL and IPP requires expression of butyrophilin BTN3A molecules on monocytes (52), which could also be affected by exercise. Future studies should determine the role monocytes play in activating and expanding TCR-γδ T-cells after exercise.…”
Section: Discussionmentioning
confidence: 99%
“…However, future applications will require a more in-depth understanding of their signaling mechanisms. Here, one new area of gd T cell research involves the role of butyrophilin in gd T cell activation (Kabelitz et al, 2017). In particular, it has been shown that butyrophilin 3A in antigen-presenting cells (APCs) is required for pAg recognition by Vg9Vd2 TCRs Hsiao et al, 2014;Palakodeti et al, 2012;Vavassori et al, 2013;Wang et al, 2013).…”
Section: Data Resourcesmentioning
confidence: 99%
“…[65, 97] At steady-state, small intestinal γδ IEL RegIIIγ production requires commensal-induced epithelial MyD88 signaling,[65] again highlighting the crucial role of microbial recognition in IEL-mediated host defense. Although human γδ T cells respond directly to microbial products through TLR stimulation and the recognition of bacterial phosphoantigens (reviewed in [98]), whether γδ IELs are also capable of directly recognizing luminal microbes has yet to be determined.…”
Section: γδ Iels Prevent Acute Bacterial Translocation Across the Epimentioning
confidence: 99%